Love-Based Curriculum in Aqidah and Akhlak Learning in Forming Students' Religious Character: islamic - Masdjudi Masdjudi; Dian Mohammad Hakim; Dwi Fitri Witri; Winarto Winarto (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the planning of the Love-Based Curriculum (LBC) in Aqidah Akhlak learning to strengthen students' religious character at MAN 1 Tulungagung, Indonesia. A qualitative field research design was employed to obtain an in-depth understanding of curriculum planning and implementation. Data were collected through classroom observations, semi-structured interviews, and document analysis involving the principal, vice principal for curriculum affairs, Aqidah Akhlak teachers, and students. Data were analyzed using Miles and Huberman's interactive model, consisting of data reduction, data display, and conclusion drawing with continuous verification through triangulation. The findings reveal that the Love-Based Curriculum is systematically planned through the establishment of a curriculum core team, formulation of short-, medium-, and long-term programs, curriculum socialization and workshops, madrasah context analysis, development of teaching resources, and integration of the Panca Cinta values into curricular and extracurricular activities. The integration of the Merdeka Curriculum with the Love-Based Curriculum strengthens Aqidah Akhlak learning by fostering compassion, empathy, tolerance, environmental responsibility, and spiritual awareness. The principal contribution of this study is the identification of madrasah context analysis as an essential stage of curriculum planning that bridges institutional characteristics, students' needs, and curriculum implementation. This finding extends existing curriculum management models by positioning contextual analysis as a strategic planning component. The proposed framework provides a practical reference for Islamic educational institutions seeking to implement value-based curricula that promote holistic character development, sustainable educational quality, and transformative learning practices.